Waterpipe (hookah) tobacco use in pregnancy: use, preferences and perceptions of flavours. (18th July 2019) - Stroud, Laura; Werner, Erika; Matteson, Kristen; Carey, Michael; Helen, Gideon St; Eissenberg, Thomas; Scott-Sheldon, Lori A J
Abstract : Objective: Waterpipe tobacco (WPT; hookah) use is common in pregnant and reproductive-age women. Sweet flavours contribute to the appeal of WPT and are a potential regulatory target. This study investigated use, preferences and perceptions of WPT flavours in pregnant WPT users, and the impact of flavour preferences on preconception/prenatal WPT use and exposure biomarkers. Methods: 58 pregnant WPT users (mean age=27 years) completed a detailed interview regarding their WPT flavours use, preferences and perceptions. Biomarkers of nicotine and carcinogen exposure (eg, cotinine, benzene, butadiene) were also collected. Results: 55% of participants were dual/poly WPT users (ie, reported use of one or more other tobacco products in addition to WPT). Pregnant WPT users reported nearly exclusive use of flavoured WPT, with greater use of menthol/mint (68%) followed by fruit flavours (48%) (p<0.001), and greater preferences for fruit followed by menthol/mint flavours (ps<0.05). Harm perceptions did not differ among flavours. Compared with dual/poly WPT users, WPT-only users reported more total WPT use events, greater use of and preference for menthol/mint flavoured WPT (ps<0.001), and decreased exposure biomarkers (ps≤0.040). Preference for menthol/mint and fruit flavours predicted more flavoured WPT use events during preconception and pregnancy; preference for menthol/mint predicted detectable cotinine and benzene levels but not butadiene. Conclusions: This is the first study of WPT flavour use, preferences and perceptions in pregnant women. Use of and preference for menthol/mint and fruit WPT flavours in this vulnerable population could be considered in regulating WPT flavours to protect the health of women and children.